Lactobacillus plantarum isolated from kefir: Protection of cultured Hep-2 cells against Shigella invasion - Kakisu, Emiliano Javier (2013)
Two types of microbial mixtures containing selected lactic acid bacteria and yeasts isolated from kefir grains were tested against the Shigella invasion of Hep-2 cells in culture. A five-strain mixture demonstrated a significant inhibition of the cell internalisation of Shigella flexneri and Shigella sonnei. The addition of single kefir strains or their mixtures to the cells, before the addition of Shigella, protected more efficiently than the simultaneous addition of the lactic-acid bacteria and Shigella on the cells. Among the kefir strains assayed, Lactobacillus plantarum strain CIDCA 83114 showed the most significant inhibition of the invasion. Both the cell walls of L. plantarum and the intact bacterial cells demonstrated an equivalent protection of cell monolayers; with the possibility of a protein or peptide mediating this effect. These results provide evidence for the potential inhibitory properties of certain kefir strains, such as L. plantarum CIDCA 83114, against disease-producing species of Shigella.